Penggunaan Kaidah Fikih Dalam Fatwa Majelis Ulama Indonesia Tentang Keuangan Syariah - Rosyadi, Imron (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
Abstact: This study aims to describe and analyze the use of legal maxims of Islamic law in the fatwas of the Indonesian Ulema Council (MUI) on Islamic finance with content analysis. MUI’s fatwas on Islamic finance are amounted to 116 fatwas, using 322 items of rules. The highest number of items according to the cluster of rules which are found on the asasîyah rules are 252 items, then kullîyah rules which well agreed have 47 items, in madhhab’s kullîyah there are 17 items, and the last on special rules have 6 items. The highest number of items by category of rules are on the principle of the third asasîyah rules, 111 items, then the principle of second asasîyah rules have 63 items. From the perspective of content analysis, the use of fikih in the MUI’s fatwas on Islamic finance considers the freedom of mu`amalah to achieve a rapid progress as far as it does not endanger the businessmen and other parties. The signposts are that business should depart from good will, adapt to the traditions of its type of business, and creatively seek solutions to business problems. All matters relating to mu`amalah involve the role of policy maker to use the principle of benefit in its policy. Key Words: Legal maxim of Islamic law, fatwa, Indonesian Ulema Council, Islamic finance.   Abstrak: Kajian ini bertujuan mendeskripsikan dan menganalisis penggunaan kaidah fikih dalam fatwa Majelis Ulama Indonesia (MUI) tentang keuangan syariah dengan analisis isi. Fatwa MUI tentang keuangan syariah berjumlah 116 fatwa, menggunakan 322 item kaidah fikih. Jumlah terbanyak item menurut rumpun kaidah terdapat pada kaidah Asasîyah sebanyak 252 item, selanjutnya kaidah kullîyah yang disepakati 47 item, kaidah kullîyah mazhab 17 item, dan terakhir kaidah khusus 6 item. Jumlah terbanyak item menurut kategori kaidah terdapat pada kaidah asasîyah ketiga sebanyak 111 item, selanjutnya kaidah asasîyah ke-2 sebanyak 63 item, dan kaidah-kaidah lainnya. Dari perspektif analisis isi, penggunaan kaidah-kaidah fikih dalam fatwa MUI tentang keuangan syariah mempertimbangkan keleluasaan mu`amalah agar mencapai kemajuan pesat sejauh usaha mu`amalah tidak membahayakan pengusaha dan pihak-pihak lainnya. Rambu-rambunya adalah usaha semestinya berangkat dari niat baik, beradaptasi terhadap tradisi jenis usahanya, dan kreatif mencari solusi atas problem-problem usaha. Semua hal yang berkaitan dengan mu`amalah melibatkan peran policy maker agar menggunakan prinsip kemaslahatan dalam kebijakannya. Kata Kunci: Kaidah Fikih, Fatwa, Majelis Ulama Indonesia, Keuangan Syariah.